Question Variations in Vocabulary Test Design in Teaching Arabic to Non-Native Speakers - kudus, Ruhul; Ulum, Fatkhul; Mariah, Enung (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2024)
In designing a vocabulary test in teaching Arabic to non-native speakers, many things must be taken into account, including the question format for the test to be a good one. This study aims to describe how to design a vocabulary test for teaching Arabic to foreign speakers, based on the criteria and principles of a good language test. This research uses qualitative approach with a desk study, and the main sources for this research are approved books such as Arabic Language Tests and Teaching Arabic to Non-Native-Speakers, and auxiliary sources such as journals, peer-reviewed articles, and textbooks such as Arabic in Your Hands. The data in this research was collected, documented and analyzed. The results showed that one of the forms of questions in the vocabulary test for non-native speakers of Arabic: Arabic vocabulary tests uses word definitions by presenting words in the target language and asking participants to determine the correct meaning of each word from the given definition. Vocabulary test completes a sentence by placing the appropriate word. Synonyms vocabulary test by selecting a suitable synonym for each given word, Synonyms vocabulary test by selecting the word corresponding to the given word. Word grouping vocabulary test by identifying the relationship between a group of words, Alignment vocabulary test by matching words with their corresponding definitions, pictures or sentences, Composition vocabulary test by arranging letters to form the correct words, Vocabulary test using words in sentence context by using given words in sentences, Picture vocabulary test by recognizing words related to the pictures presented This study concluded that vocabulary test design is important to measure students' ability and understanding of Arabic vocabulary. Therefore, the vocabulary assortment must be correctly shaped to be a good vocabulary test design and according to the standards and principles of a good language test.